Test‐dose pharmacokinetics guided melphalan dose adjustment in reduced intensity conditioning allogeneic transplant for non‐malignant disorders. Issue 1 (13th June 2021) - Chandra, Sharat; Mizuno, Kana; Zhao, Junfang; Davies, Stella M.; Marsh, Rebecca A.; Fukuda, Tsuyoshi; Setchell, Kenneth D. R.; Vinks, Alexander A.; Mehta, Parinda A.
Abstract : Aims: We studied melphalan pharmacokinetics (PK) and feasibility of melphalan full‐dose adjustment based on test‐dose PK in children and young adults with non‐malignant disorders (NMD) undergoing allogeneic hematopoietic cell transplantation (HCT) using reduced intensity conditioning (RIC) containing alemtuzumab, fludarabine and melphalan. Methods: Patients received test‐dose melphalan (10% of planned full‐dose) prior to conditioning. Blood samples for PK were obtained around test and full‐dose melphalan (140 mg/m 2 or 4.7 mg/kg in patients <10 kg). Melphalan concentration was measured by liquid chromatography electrospray ionization tandem mass‐spectrometry assay and data were analysed using a population‐PK model and Bayesian estimation. Test and full‐dose melphalan clearance estimates were evaluated by pairwise Wilcoxon test and Bland–Altman plot. Results: Twenty‐four patients undergoing 25 transplants were included in the final analysis. Patients received standard full‐dose melphalan in 17 transplants, with median area under the concentration–time curve (AUC) of 5.5 mg*h/L (range, 3.0–9.5 mg*h/L). Patients received test‐dose melphalan in 23 transplants with a test‐dose PK predicted full‐dose AUC range of 2.9–16.8 mg*h/L. In seven transplants where patients had baseline organ impairment, test‐dose PK predicted higher exposure for standard full‐dose (median AUC 13.8 mg*h/L). Melphalan full‐dose was adjusted in these patients, with achievement of desired target AUC (3.6–5.4 mg*h/L) and no excess toxicity. Mean ratio of test‐dose clearance to full‐dose clearance was 1.03. Twenty of 22 patients (91%) were within the 95% confidence intervals of the clearance ratio. Conclusion: Melphalan test‐dose PK reliably predicts full‐dose PK and allows for accurate adjustment of full‐dose melphalan in RIC‐HCT for NMD. This approach can avoid excess toxicity from increased systemic exposure, especially in patients with organ impairment.